Recreational strategies for developing listening skill on the students of eighth grade of basic education at colegio nocturno Tungurahua, Baños, province of Tungurahua, during the first term, 2012 - 2013 school year - Luzuriaga Ochoa, María Viviana (2016)
Recreational Strategies for developing listening Skills on the students of Basic Education at Colegio Nocturno Tungurahua, Baños, Province of Tungurahua, during the first Term 2012-2013 School year", is a practical research project that contains some practical Recreational Strategies and explains how could be used teaching English in class with participation of a group of 30 students between the ages 14 to 18 years old. This work wants to describe the login problem of the research: The problem tree shows the causes and effects, the Problem Formulation, the Variables, the Objectives and Justification. Moreover, it has a theoretical framework, based on five chapters; Part One is about Problem Identification, Problem Formulation, Core Problem, Variables Matrix, Objective General and Objective Specifics, Justification. Part two content Theoretical Framework where include, The School, Mission, the Vision, the Values, and the institution Infrastructure. Also include Recreational Strategies.